Use of Audio-Visual Teaching Learning Materials in Facilitating of Health Education in Early Childhood Development Centers, Pokhara, Nepal - Pant, Indira; Sharma, Laxmi Kanta; Sharma, Mohan Kumar (Journal of Health Promotion, 2024)
Early Childhood Development (ECD); is a crucial period for nurturing the physical, cognitive, social, emotional, and linguistic growth of children aged three to eight.  The study aims to assess the factors influencing the use of audio-visual teaching and learning materials in facilitating health education in the ECD centersin Pokhara, Nepal. The research utilized a quantitative, cross-sectional research design. Data were collected using face-to-face interviews with 486 respondents from 33 selected ECD centers. The participants were randomly selected using proportionate sampling from each selected ECD center. The descriptive analysis employed for univariate and bivariate analyses using Statistical Package of Social Science (SPSS) 25 version. Variables such as school type, facilitator qualification, management of learning materials, availability of potable water and sanitation facilities, learning corner condition, and classroom decoration were significantly associated with using audio-visual aids, p